Tratamiento farmacológico de las neoplasias asociadas con la enfermedad de von Hippel-Lindau. Revisión Sistemática - Veronica Hurtado Hurtado; Cristina Cabrera Mañay; Patricia Tamayo Aguilar (Oncología)
Background: Von Hippel-Lindau disease is an autosomal dominant syndrome characterized by the development of benign and malignant tumors throughout life. For many years, neoplasms associated with this disease were treated by surgical resection or ablation with the aim of reducing the risk of metastatic disease and controlling local or systemic sequelae. An effective systemic alternative could reduce the surgical burden and represents a new approach to oncological treatment.